Dying for mercy - Clark, Mary Jane Behrends (New York : Avon, 2010)
A fabled estate becomes a twisted puzzle involving secrets and murder, in this fast-paced thriller featuring the KEY News sleuths introduced in'It Only Takes a Moment' and'When Day Breaks.'
Keywords: Women journalists -- Fiction; Rich people -- Crimes against -- Fiction; Serial murderers -- fiction; Tuxedo Park (N.Y.) -- Fiction